Is sodium supplementation necessary to avoid dehydration during prolonged exercise in the heat? - Hoffman, M. D.; Stuempfle, K. J. (The Journal of Strength and Conditioning Research, 2016)
The primary purpose of this work was to gain further insight into the need for sodium supplementation for maintenance of appropriate hydration during prolonged exercise under hot conditions. Participants of a 161-km ultramarathon (ambient temperature reaching 39° C) underwent body weight measurements immediately before, during, and after the race, and completed a postrace questionnaire about supplemental sodium intake and drinking strategies during 4 race segments. The postrace questionnaire was completed by 233 (78.7%) race finishers. Significant direct relationships were found for percentage weight change during the race with intake rate (r = 0.18, p = 0.0058) and total amount (r = 0.24, p = 0.0002) of sodium in supplements. Comparing those using no sodium supplements throughout the race (n = 15) with those using sodium supplements each race segment (n = 138), body weight change across the course showed significant group (p = 0.022), course location (p < 0.0001), and interaction (p = 0.0098) effects. Posttests revealed greater weight loss at 90 km (p = 0.016, -3.2 ± 1.6% vs. -2.2 ± 1.5%, mean ± SD) and the finish (p = 0.014, -3.2 ± 1.5% vs. -1.9 ± 1.9%) for those using no sodium supplements compared with those using sodium supplements each segment. Six runners who used no sodium supplements, drank to thirst, and only drank water or a mixture of mostly water with some electrolyte-containing drink finished with mean weight change of -3.4%. Although the use of supplemental sodium enhanced body weight maintenance, those not using sodium supplements maintained a more appropriate weight than those consistently using sodium supplements. Therefore, we conclude that the supplemental sodium is unnecessary to maintain appropriate hydration during prolonged exercise in the heat.